Analisis Yuridis Kekuatan Hukum Memorandum Of Understanding Yang Timbul Karena Hubungan Perdata Internasional Antara Negara Indonesia Dan Negara Australia - Devie Devie (Journal of Law and Policy Transformation, 2020)
Cooperation relationships governed by international civil law in the business world between 2 (two) countries or more generally use written agreements to obtain legal certainty for both parties and as a manifestation of good faith / good faith in establishing work relations. The form of cooperation in business between countries is often not made in a permanent form, on the grounds that it is only in the form of an agreement or an initial agreement, there are negotiations until only for consideration. This then becomes the background for the birth of a Memorandum of Understanding in business agreements between countries. The Memorandum of Understanding was initially only considered as a preliminary agreement that has no legal force in binding and forcing the parties concerned to fulfill their obligations and cannot be used as a means of proof in a court of law, this is the view of the general public and the court in a country adhering to the common legal system law, one of which is the state of Australia, whereas according to the Indonesian state which has no law in regulating the Memorandum of Understanding has the legal force in binding and forcing it like any other formal agreement, if it is linked to the Civil Code. The method used in researching this thesis is a type of normative legal research as a guideline for writing, where the author collects data through library research or the results of library studies by reviewing the laws of Indonesia and Australia as the main data in writing this thesis report with the help of journals -journals obtained from electronic means that discuss problems in this thesis report so that the author can conclude from the problem under study. Based on the results of research conducted by researchers, it can be concluded that a Memorandum of Understanding can be formed by two countries with different legal systems with the aim of creating a binding cooperative relationship and has the power to force both parties to fulfill obligations if there is an agreement between parties to state in the form of a Memorandum of Understanding there is an "intention to create legal relations" or intention to form a legal relationship.